Clinical benefits of a Bayesian model for plasma-derived factor VIII/VWF after one year of pharmacokinetic-guided prophylaxis in severe/moderate hemophilia A patients. Issue 205 (September 2021) - Megías-Vericat, Juan Eduardo; Bonanad, Santiago; Haya, Saturnino; Cid, Ana Rosa; Marqués, María Remedios; Ferrada, Alejandra; Monte-Boquet, Emilio; Pérez-Alenda, Sofía; Bosch, Pau; Querol-Giner, Felipe; Poveda, Jose Luis
Abstract: Introduction: Individual pharmacokinetic (PK) profiling in hemophilia A (HA) helps to individualize prophylaxis using population PK models (popPK). A specific popPK model for plasma-derived factor VIII containing von-Willebrand Factor (pdFVIII/VWF) was developed. Aim: To compare standard versus PK-driven prophylaxis, using a generic or a specific popPK model for pdFVIII/VWF. Materials and methods: A prospective study conducted in HA patients in prophylaxis with pdFVIII/VWF (Fanhdi®) comparing three one-year study periods: (1) standard prophylaxis, (2) PK-guided prophylaxis using a generic pdFVIII popPK model which described FVIII activity irrespective of FVIII concentrate, and (3) PK-guided prophylaxis with specific pdFVIII/VWF popPK model. PK parameters analyzed were half-life, trough levels (TL) at 24, 48 and 72 h, and time to reach FVIII levels of 1, 2, 5% (T5%). Clinical outcomes were dose/kg, FVIII consumption, annualized bleeding rate (ABR), annualized joint bleeding rate (AJBR), spontaneous and traumatic bleeds. Results: Of the 30 analyzed patients, 28 had severe HA and the median age was 31.2. Fifteen patient's prophylaxis doses were PK-adjusted. After the generic PK-guided prophylaxis period, younger patients showed more joint bleeds, a shorter half-life, and lower TL48, TL72 and T5%. Using the specific pdFVIII/VWF popPK model compared with standard prophylaxis, a lower spontaneous AJBR was observed in the entire cohort and in patients aged >15 years. Additionally, lower spontaneous ABR was reported in patients aged ≤15 years comparing specific and generic models. Conclusions: PK-guided prophylaxis with a specific pdFVIII/VWF popPK model allowed treatment individualization and improved bleeding control in routine clinical practice, especially in younger patients with short pdFVIII/VWF half-lives. Highlights: Bayesian pharmacokinetic-guided prophylaxis optimizes hemophilia A (HA) treatment. We assessed a specific population PK (popPK) model for pdFVIII/VWF in HA. The specific pdFVIII/VWF popPK model allowed treatment individualization. The pdFVIII/VWF popPK model improved bleeding control in HA patients. Pharmacokinetic-guided prophylaxis did not increase pdFVIII/VWF consumption.